The medical education in Poland and COVID-19 pandemic – opportunities and threats - Skowron, Adam; Sytnik-Czetwertyński, Janusz (Journal of Education, Health and Sport, 2021)
The article presents the impact of the COVID-19 pandemic on medical education in Poland, with particular emphasis on the analysis of opportunities and threats resulting from the current pandemic situation. The main part of the article presents the problems of medical education in the era of the COVID-19 pandemic both in specific and in general - global dimensions. As it turns out, some of the problems associated with medical education in times of pandemics have an universal character.